2017
DOI: 10.1111/febs.14132
|View full text |Cite
|
Sign up to set email alerts
|

hsa_circ_0013958: a circular RNA and potential novel biomarker for lung adenocarcinoma

Abstract: Circular RNAs (circRNAs) are associated with cancer progression and metastasis, although little is known about their role in lung adenocarcinoma (LAC). In the present study, microarrays were first used to screen for tumour-specific circRNA candidates in LAC tissue. Thirty-nine circRNAs were found to be up-regulated and 20 were down-regulated (fold change > 2.0). Among them, hsa_circ_0013958 was further confirmed to be up-regulated in all of the LAC tissues, cells and plasma. In addition, hsa_ circ_0013958 leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
193
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(196 citation statements)
references
References 39 publications
2
193
0
1
Order By: Relevance
“…Numerous studies had confirmed the abnormal expression levels of some circRNAs and miRNAs in diverse types of cancers. For instance, hsa_circ_0013958 was confirmed to be upregulated in all of the LAC tissues, cells and plasma . Circ‐FBXW7 was abundantly expressed in the normal human brain, and circ‐FBXW7 expression positively associated with glioblastoma patient overall survival .…”
Section: Discussionmentioning
confidence: 93%
“…Numerous studies had confirmed the abnormal expression levels of some circRNAs and miRNAs in diverse types of cancers. For instance, hsa_circ_0013958 was confirmed to be upregulated in all of the LAC tissues, cells and plasma . Circ‐FBXW7 was abundantly expressed in the normal human brain, and circ‐FBXW7 expression positively associated with glioblastoma patient overall survival .…”
Section: Discussionmentioning
confidence: 93%
“…circ_100290 could play a role of endogenous competitive RNA with the miR-29 family to regulate the expression of CDK6 in the development of oral cancer [18]. circ_0013958 played a role of miR-134 sponge and regulate the expression of cyclin D1 protein in the development of non-small cell lung cancer [19]. circ_100269 is down regulated in gastric cancer and inhibits the growth of gastric cancer cells by targeting miR-630 [20].…”
Section: Introductionmentioning
confidence: 99%
“…Among the included publications, a total of 43 articles on 64 studies were analyzed involving 10,123 subjects in Table . Of the 64 studies, five studies focused on colorectal cancer (Ji et al, ; Wang, Li, et al, ; Wang et al, ; Zhang, Yang, et al, ; Zhuo, Lin, Chen, Huang, & Hu, ), 10 on breast cancer (Lu et al, ; Yin et al, ), 22 on gastric cancer (Chen, Li, Zhao, Xiao, & Guo, ; Huang, He, Liang, Huang, & Zhu, ; Li, et al, , ; Li, Shao, et al, ; Li, Song, et al, ; Lu et al, ; Lu, Shao, Ye, Xiao, & Guo, ; Shao, Chen, et al, ; Shao, Li, et al, ; Shao, Yang, et al, ; Sun, Tang, et al, ; Tian, Chen, Li, & Xiao, ; Wei et al, ; Xie et al, ; Zhao, Chen, Li, Xiao, & Zhang, ), four on lung cancer (Li, Wang, Chen, Chen, & Jin, ; Zhu et al, ; Zong et al, ), 16 on hepatocellular carcinoma (Chen, Zhang, Lin, Song, & Wang, ; Fu et al, , ; Li et al, ; Qin et al, ; Shang et al, ; Yao et al, ; Yao et al, ; Zhang, Zhang, Lin, & Wang, ; Zhang, Zhou, et al, ; Zhang, Xu, et al, ) and seven on other cancers (Fan, Cao, Liu, Zhang, & Li, ; Lan et al, ; Li et al, ; Sun, Li, et al, ; Teng et al, ; Wang, Xue, et al, ; Yang et al, ). Moreover, three articles with 13 studies explored the diagnostic value of the combined circRNAs (Chen, Li, Zhao, et al, ; Fan et al, ; Li, Shao, et al, ) in Table .…”
Section: Resultsmentioning
confidence: 99%
“…In the past decade, because of their special advantages as biomarkers, circRNAs have attracted attention in the detection, diagnosis, and prognosis of cancers (Chen, Li, Zheng, et al, ; Jiang et al, ; Shang et al, ; Zhang et al, ; Zhu et al, ). First, dysregulation of circRNAs was identified in tissues, plasma, and even exosomes from patients with many types of cancer (Li, Song, et al, ; Lu et al, ; Shao, Chen, et al, ).…”
Section: Discussionmentioning
confidence: 99%